Arte como necessidade de vida: uma construção de processos criativos em pinturas autorais [2020-2023] - Nunes, Luciene Torres de Carvalho (2023)
This Dissertation is a research within the line of Creative Processes in Visual Arts with a production that is part of art, life and creation, an intertwined term to understand art as a necessity of life of the subject I, woman, white, artist, Brazilian, northeastern, whose art production specifically expresses what I experienced in the city of Recife, from 2020 to 2023, including the pandemic period of covid 19, in a large Brazilian urban city that had similar impacts in other large cities in Brazil and the world . I tried to create a poetic with the experiences in this context of isolation, new sanitary habits, social reorganization, violence, social inequality, gender issues, all inserted in a disastrous and polarized political environment, thus I present and fragment this time in the language of contemporary painting and its poetic possibilities with the series, Arte Como Necessidade de Vida, whose first works participated in an exhibition at the beginning of 2022, where I also present the sketches, drawings, color choices, time logistics, materials and other information that lead to say that I finished part of a set of works from an artist's life. The construction of this visual poetics in painting, an ancient and traditional language, is a persistence in the arts bringing reflections on the subject and society, and as for the investigation of this artistic work, I rely on the guiding supports of literature, Gesto Inacabado (2012) by Cecilia A. Salles , The Malaise of Post-Modernity (1998) by Zygmunt Bauman (1925 – 2017) and The Persistence of Painting by Gaudêncio Fidelis and Paulo Sérgio Duarte (2005).